La universalización de la educación artística en la enseñanza argentina : acciones estratégicas en la formación superior de docentes de arte - Maddonni, Alejandra (2018)
This article describes and analyzes actions as a whole spread out during the last years in the development of the Artistic Education in Argentina. This development is focused in the visual arts teachers’ superior training and attempts to demon-strate the importance of the redefinition of its teaching practices as professional teachers politically committed with the formation of critical citizens